2012
DOI: 10.1038/modpathol.2012.113
|View full text |Cite
|
Sign up to set email alerts
|

Papillary mucinous metaplasia of the endometrium as a possible precursor of endometrial mucinous adenocarcinoma

Abstract: Mucinous adenocarcinoma is an uncommon type of endometrial adenocarcinoma for which precursor lesions have yet to be clarified. During a review of noncancerous endometrial lesions in postmenopausal women, we found that mucinous endometrial glands showed variable degrees of epithelial changes that ranged from the formation of simple tubular glands to the formation of complex glands with papillary tufts, and some of the glands with papillary tufts were architecturally similar to low-grade mucinous adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…14 More recently, KRAS mutation was found in a high proportion of a small, highly selected cohort of complex, papillary mucinous lesions of the endometrium. 11 Similar to the latter, the current study also identifies a significant difference in the prevalence of KRAS mutation between simple and complex mucinous lesions (0% vs 55%). Patients with KRAS mutation had a PPV of 88% (7 of 8 cases) of having atypical complex hyperplasia or carcinoma in their follow-up hysterectomy specimens, although this value dropped to 67% (10 of 15 cases) if all types of follow-up specimens including curettage and hysterectomy were considered.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…14 More recently, KRAS mutation was found in a high proportion of a small, highly selected cohort of complex, papillary mucinous lesions of the endometrium. 11 Similar to the latter, the current study also identifies a significant difference in the prevalence of KRAS mutation between simple and complex mucinous lesions (0% vs 55%). Patients with KRAS mutation had a PPV of 88% (7 of 8 cases) of having atypical complex hyperplasia or carcinoma in their follow-up hysterectomy specimens, although this value dropped to 67% (10 of 15 cases) if all types of follow-up specimens including curettage and hysterectomy were considered.…”
Section: Discussionsupporting
confidence: 78%
“…We did not further subclassify complex mucinous lesions, as recent immunohistochemical and molecular genetic investigations indicated that complex mucinous lesions with varying complexity and cytological abnormalities share similar oncogenic profiles as possible precancerous lesions at least for a subset of endometrial adenocarcinomas. 11 In our study, 54% (14/35) of patients with complex mucinous changes were found to have complex atypical hyperplasia or adenocarcinoma in their follow-up curettage or hysterectomy specimens. In a study by Nucci et al, 3 the majority of complex mucinous lesions were found to have endometrial carcinoma in the follow-up hysterectomy.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations